East-Siberian Zodchestvo Festival - 2012 - Tkacheva, Marina (project baikal, 2012)
Catalogue East-Siberian Zodchestvo Festival 2012 Chronicle of the East-Siberian Zodchestvo Festival 2012 Our Guest, Totan Kuzembaev The List of Participants of the East-Siberian Zodchestvo Festival XII Built Projects Un-built Projects Propaganda of Architecture Creation of Young Architects and Students Children’s Architectural and Artistic Creation